Les croyances des étudiants sur la nature de leur intelligence : un facteur de participation dans des dispositifs d’aide à la réussite? - Xavier Massart; Aveline Mazy; Karine Dejean; Marc Romainville (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
For several years, universities have offered numerous support systems for first-time students to help them succeed. These systems do not always reach students who have the most difficulty in learning. This is the case of the success aid system discussed in this article, which aims to remedy the lack of mastery of prerequisites for newcomers to university, whereas Vieillevoye et al. (2012) have shown a correlation between mastery of these and success at the end of the year. The mastery of the prerequisites is assessed here with the help of tests (called 'Passports pour le bac'). The aim of this article is to try to understand why some students do not participate in the tested prerequisite reinforcement sessions when they have received feedback informing them of the lack of mastery of prerequisites. Our hypothesis is that Dweck's (2010) work on the links between 'state of mind' (people's beliefs about their intelligence) and their attitudes to failure in terms of engagement in remedial activities may provide some insight into this low student participation rate. Therefore, the present study aims to investigate first the students' state of mind at the beginning of their university studies and then to analyse a possible relationship between this state of mind and the importance they give to prerequisites and the need (as well as the possibility) to remedy possible deficiencies. Results presented are based on a questionnaire submitted to a large population: 1,585 first-time students from the University of Namur and the University Saint-Louis of Bruxelles. These results are further analysed in the light of a number of qualitative interviews conducted subsequently.